STALKING AND CYBERSTALKING AS A FORM OF VIOLENCE - Siemieniecka, Dorota; Skibińska, Małgorzata (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2019)
Experiencing violence is one of the greatest threats to human freedom and security. Consequences of violence, both physical - such as bruises, cuts, fractures, and even death, as well as mental - aggression, mental health problems, low self-esteem, emotional and cognitive disorders, can be drastic and permanent for the victim. Widespread and easy access to the media increases the risk of experiencing violence and its consequences. It is therefore important to make the public aware of possible types of violence and to conduct research in this area to help specialists in the field of psychology, law, pedagogy and psychotherapy as well as law enforcement agencies and network service providers to create effective prevention strategies.